2007
DOI: 10.1097/mlg.0b013e318123f2e7
|View full text |Cite
|
Sign up to set email alerts
|

The Supraglottic Nerve Supply: An Anatomic Study With Clinical Implications

Abstract: Our results may contribute to a better understanding of supraglottic actions that provide primary functions of the larynx (such as swallowing, coughing, and breathing). An enhanced knowledge of neurolaryngology also provides a basis for interpreting disorders or paralyzes following surgical treatments (e.g., thyroid surgery, partial laryngectomy) and helps to lower the risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 16 publications
0
27
0
2
Order By: Relevance
“…According to the literature, the ELN is a linear nerve trunk (Olthoff et al 2007;Oliveira and Silva 2007). Based on a study of 60 adult cadavers, Sun and Chang (1991) reported that the superior laryngeal nerve (SLN) and its branches often connected with one or more branches from the cervical sympathetic chain (CSC) to form an SLN loop.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the ELN is a linear nerve trunk (Olthoff et al 2007;Oliveira and Silva 2007). Based on a study of 60 adult cadavers, Sun and Chang (1991) reported that the superior laryngeal nerve (SLN) and its branches often connected with one or more branches from the cervical sympathetic chain (CSC) to form an SLN loop.…”
Section: Introductionmentioning
confidence: 99%
“…Innervation for supraglottic structures via the superior laryngeal nerve is distinct from most of the intrinsic laryngeal muscles, which are innervated via the recurrent laryngeal nerve. 89 All of the participants in the current study demonstrated complete TVF …”
Section: Tvf Kinematics During Coughmentioning
confidence: 99%
“…Because of the contiguity with the superior thyroid artery, iatrogenic lesions of the ESLN in thyroidectomies are mentioned in the literature [9][10][11][12] . It is reasonable to assume that iatrogenic injuries, which may involve the superior parathyroid glands, are influenced by anatomical variations of the nerve in relation to the short vertical segment of the superior thyroid artery before it penetrates the gland, since the superior thyroid vein usually lies more laterally in relation to the cranial border of the thyroid lobe; thus, farther from the nerve [13][14][15][16][17] .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…Also as a result of the anastomoses, the motor functions of the ESLN include phonation, the protection of the airways against aspiration during swallowing, and optimization of breathing [6][7][8][9] .…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%